Rodent models of heart failure: an updated review - Gomes, AC (2013)
Heart failure (HF) is one of the major health and economic burdens worldwide, and its prevalence is continuously increasing. The study of HF requires reliable animal models to study the chronic changes and pharmacologic interventions in myocardial structure and function and to follow its progression toward HF. Indeed, during the past 40 years, basic and translational scientists have used small animal models to understand the pathophysiology of HF and find more efficient ways of preventing and managing patients suffering from congestive HF (CHF). Each species and each animal model has advantages and disadvantages, and the choice of one model over another should take them into account for a good experimental design. The aim of this review is to describe and highlight the advantages and drawbacks of some commonly used HF rodents models, including both non-genetically and genetically engineered models, with a specific subchapter concerning diastolic HF models.